Trends in COPD prevalence and exacerbation rates in Dutch primary care - Bischoff, Erik WMA (Royal College of General Practitioners, 2009)
BACKGROUND: Changes in the burden of chronic obstructive pulmonary disease (COPD) and its exacerbations on primary health care are not well studied. AIM: To identify trends in the prevalence of physician-diagnosed COPD and exacerbation rates by age, sex, and socioeconomic status in a general practice population. DESIGN OF STUDY: Trend analysis of COPD data from a 27-year prospective cohort of a dynamic general practice population. SETTING: Data were taken from the Continuous Morbidity Registration Nijmegen. METHOD: For the period 1980–2006, COPD and COPD exacerbation data were extracted for patients aged ≥40 years. Data were standardised for the composition of the Continuous Morbidity Registration population in the year 2000. Regression coefficients for trends were estimated by sex, age, and socioeconomic status. Rate ratios were calculated for prevalence differences in different demographic subgroups. RESULTS: During the study period, the overall COPD prevalence decreased from 72.7 to 54.5 per 1000 patients per year. The exacerbation rate decreased from 44.1 to 31.5 per 100 patients, and the percentage of patients with COPD who had exacerbations declined from 27.6% to 21.0%. The prevalence of COPD increased significantly in women, in particular those aged ≥65 years with low socioeconomic status. Decreases in exacerbation rates and percentages of patients with exacerbations were independent of sex, age, and socioeconomic status. CONCLUSION: The decline in COPD prevalence and exacerbation rates suggests a reduction of the burden on Dutch primary care. The increase of the prevalence in women indicates a need to focus on this particular subgroup in COPD management and research.